Enhancing blockchain quality-of-service: a comparative analysis and novel smart contract mechanism - Alock Gupta; Kamlesh Lakhwani (Discover Applied Sciences)
Abstract This article presents an innovative contract framework to improve Quality-of-Service (QoS) within the CoreDAO blockchain, focusing on the 9NFTMania token. The research is driven by the need for reliable, decentralized processes that improve data security and transaction efficacy inside CoreDAO. The proposed Solidity-based smart contract incorporates easy reflection, liquidity provision, fee processing, and secure token transfers. The development process included criteria definition, research, contract design, platform selection, coding, rigorous testing, and real-time maintenance to ensure functionality and security. The enhancements to the ERC20 token standard improved liquidity, token exchange, and ownership management. A Dividend Token contract introduced governance mechanisms, fee structures, liquidity availability, and tax settings. Comparative analysis demonstrates the framework’s superior accuracy, precision, recall, and F1-score performance compared to conventional mechanisms. Quantitative metrics highlight significant improvements in data security, transaction efficiency, and blockchain scalability, particularly in healthcare applications. By using PoS systems, the suggested structure essentially improves CoreDAO’s quality of service—especially for the 9NFT Mania token. It adds to a safe, scalable, and effective blockchain ecosystem by surpassing the transaction efficiency and scalability of conventional Proof-of-Work methods.